FcεRI, but Not FcγR, Signals Induce Prostaglandin D2 and E2 Production from Basophils - Ugajin, Tsukasa (American Society for Investigative Pathology, 2011)
Prostaglandin (PG) D2 and PGE2 are arachidonic acid metabolites that are generated though an isomerization reaction catalyzed by PG synthases. PGs have been implicated in immunologic reactions in addition to a wide range of physiological functions. It has long been thought that basophils, in contrast to mast cells, do not synthesize PGs, although they do release leukotrienes and platelet-activating factor. Here, we show that basophils function as a source of PGD2 and PGE2. In vitro-cultured basophils from mouse bone marrow produced both PGD2 and PGE2 in response to IgE + antigen (Ag), but not to IgG + Ag. Release of PGs was almost completely abrogated in cultured basophils from FcRγ-chain(−/−) mice, indicating the involvement of FcεRI. Basophils freshly isolated from bone marrow cells (primary basophils) were also capable of secreting PGD2 and PGE2. Although the amount of PGD2 released from primary basophils was lower than that from mast cells, the capability of primary basophils to generate PGE2 was more potent than that of mast cells. Transcripts and proteins for both hematopoietic-type PGD synthase and PGE synthase were detected in basophils. In addition, human basophils, like mouse basophils, also produced PGD2 through IgE-mediated stimulation. Thus, basophils could be an important source of PGD2/PGE2 and may contribute to allergic inflammation and immune responses.